2022
DOI: 10.1177/23780231211072683
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents Matter for Student Loan Repayment after Graduation?

Abstract: Previous studies suggest that a college degree is the great equalizer leveling the playing field. However, the rapidly growing educational debt of college graduates might restrict their life chances throughout adulthood, particularly for those raised in socioeconomically disadvantaged families. This study uses data from the National Survey of College Graduates to examine whether parents’ socioeconomic status is related to their children’s student loan repayment after graduation. Holding the amount borrowed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…However, despite the rapid expansion of higher education during recent decades, the decline in the proportion of non-college-educated youth has slowed since 2010 (Hussar et al 2020). The privatization of higher education and rising tuition costs may continue to limit college access for racially marginalized youth (Goldin and Katz 2009; Oh 2022). In addition, our empirical findings imply that policy geared toward addressing social inequality in premarket factors would not fully address racial/ethnic and gender earnings disparities among non-college-educated youth.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the rapid expansion of higher education during recent decades, the decline in the proportion of non-college-educated youth has slowed since 2010 (Hussar et al 2020). The privatization of higher education and rising tuition costs may continue to limit college access for racially marginalized youth (Goldin and Katz 2009; Oh 2022). In addition, our empirical findings imply that policy geared toward addressing social inequality in premarket factors would not fully address racial/ethnic and gender earnings disparities among non-college-educated youth.…”
Section: Discussionmentioning
confidence: 99%
“…A study using the National Survey of College Graduates found that family background and social supports greatly in uenced a students' likelihood of successful student loan repayment, suggesting that those students with a high socioeconomic status are in a better nancial position due to their social supports. 13 Another study found that, among a cohort of undergraduate students, there was an interaction effect between nancial stress, general anxiety, and family social supports. 14 The authors speculated that general social support might also have a moderating effect, but due to the limited scope of their sample, this effect was not observed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bahadir and Gicheva (2019) found that higher student-debt-to-income ratios caused a reduction in state-level consumption. Moreover, the burgeoning student debt crisis has been associated with increases in the racial wealth gap (Percheski and Gibson-Davis 2020), and when considering the influence of parent’s education level on children’s student loan repayments, student debt can be seen as a limit to the meritocratic power of higher education (Oh 2022). Thus, given the size and breadth of student debt holding, the burdens it can have on individuals and communities, and the potential to address student loan burdens through executive—rather than legislative—action (Minsky 2022), student debt forgiveness has received increasing attention from policymakers, the media, researchers, and advocacy groups in recent years.…”
mentioning
confidence: 99%